Pengaruh Program Pembinaan Mahasiswa Wirausaha (P2MW) Terhadap Minat Berwirausaha Melalui Locus Of Control Sebagai Variabel Intervening Pada Mahasiswa Universitas Negeri Surabaya - Rival Dani Ardiansyah; Saino Saino (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study was conducted to determine the influence of entrepreneurial interest on Surabaya State University students after participating in the entrepreneurial student development program (P2MW) through locus of control as an intervening variable. This study used quantitative methods. The population in this study is Surabaya State University students who take part in the entrepreneurial student coaching program. The sample used was 90 respondents using saturated sampling techniques. The criteria for respondents to this study were students who participated in the entrepreneurial student development program organized by the Ministry of Education and Culture and Technology, the data analysis test techniques used were classical assumption tests, path analysis, and hypothesis tests processed using the IBM 25 version of the SPSS program. The results of this study did not have a significant effect on entrepreneurial student development interest. There is a significant influence of entrepreneurial student development programs on the locus of control. There is a significant influence of locus of control on entrepreneurial interest. The entrepreneurial student coaching program towards entrepreneurial interest through locus of control can mediate the variables of the entrepreneurial student coaching program and entrepreneurial interest. Keywords: Entrepreneurial Student Development Program, Locus of Control, Entrepreneurial Interest